2022
DOI: 10.1175/wcas-d-21-0132.1
|View full text |Cite
|
Sign up to set email alerts
|

How Is COVID-19 Affected by Weather? Metaregression of 158 Studies and Recommendations for Best Practices in Future Research

Abstract: Because many viral respiratory diseases show seasonal cycles, weather conditions could affect the spread of COVID-19. Although many studies pursued this possible link early in the pandemic, their results were inconsistent. Here, we assembled 158 quantitative empirical studies examining the link between weather and COVID-19. A meta-regression analysis was performed on their 4,793 correlation coefficients to explain these inconsistent results. We found four principal findings. First, 80 of the 158 studies did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 74 publications
0
15
1
1
Order By: Relevance
“…Intervention or environmental variables may also be included in this regression. For example, there is increasing evidence of links between COVID infection and weather conditions [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intervention or environmental variables may also be included in this regression. For example, there is increasing evidence of links between COVID infection and weather conditions [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent metaregression of 158 studies conducted by Tan et al (2022) revealed that Asian countries had more positive associations between COVID-19 spread and rising temperatures compared to other regions. In addition, regardless of the statistical analytic method or geographic location, increased sun energy was linked to reduced COVID-19 spread [377].…”
Section: Temperature Humidity and Wind Speedmentioning
confidence: 95%
“…R t = 1.8-3.1 in December 2021 (Italy) [346]. R t = 1.34-3.57 depending on the location and vaccination rate, according to data obtained in many areas as of January 2022 (India) [377].…”
Section: Sars-covmentioning
confidence: 99%
“…Though several studies have indicated that meteorological factors could influence the spread of COVID-19, inconsistencies remain regarding effect size and direction for temperature, humidity and ultraviolet (UV) radiation ( Byun et al, 2021 ; Chen et al, 2022 ; Jerrett et al, 2022 ; Kaplin et al, 2021 ; Li et al, 2022 ; Majumder and Ray, 2021 ; Romero Starke et al, 2021 ; Zheng et al, 2021 ). Explanations for these inconsistencies might include residual confounding due to pharmacological or non-pharmacological interventions ( Chen et al, 2022 ; Nottmeyer et al, 2022 ), differences in virus lineage and variant in different regions and populations ( Neagu et al, 2021 ; Zhao et al, 2022 ), changes in season or geospatial scale considered, and other factors ( Babin, 2020 ; Kerr et al, 2021 ; Li et al, 2022 ; Tan and Schultz, 2022 ). Additional uncertainty stems from the unknown lag time between meteorological determinants and COVID-19 endpoints, if they do have an effect ( Xiao et al, 2021 ), or the possibility that weather variables have indirect effects mediated through changes in mobility, social contacts and other behavioral variables ( Barceló and Saez, 2021 ; Paraskevis et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%